1983
DOI: 10.1007/bf01295815
|View full text |Cite
|
Sign up to set email alerts
|

Colonic transport of water and electrolytes in a patient with secretory diarrhea due to collagenous colitis

Abstract: Whole colon perfusion studies and measurements of luminal prostaglandin E2 were carried out in a 41-year-old female with collagenous colitis to investigate pathophysiological mechanisms for the diarrhea. Biopsies of the colorectal mucosa had revealed a continuous 25- to 60-micron subepithelial collagenous layer, but normal junctional complexes and capillaries. When the patient fasted, the diarrhea persisted and fecal electrolytes, as estimated from the concentration of sodium, potassium, and their anions, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…8 Collagenous colitis is diagnosed by histological examination of colonic biopsies, which shows the characteristic band of collagen deposited beneath the epithelial basement membrane, usually associated with a non-specific chronic inflammatory infiltrate. The relationship between the inflammatory reaction, the collagen deposition and the development of symptoms is uncertain, and the stimulus to collagen deposition is also unknown.…”
Section: Discussionmentioning
confidence: 99%
“…8 Collagenous colitis is diagnosed by histological examination of colonic biopsies, which shows the characteristic band of collagen deposited beneath the epithelial basement membrane, usually associated with a non-specific chronic inflammatory infiltrate. The relationship between the inflammatory reaction, the collagen deposition and the development of symptoms is uncertain, and the stimulus to collagen deposition is also unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion studies in 4 patients showed net secretion of fluid and electrolytes in the colon and the small intestine and no sodium absorption in the colon [5, 6, 7]. In one of these patients, diarrhoea persisted during fasting [7]. In another study fasting normalised stool output in 2 of 4 patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports concerning the mechanisms of diarrhoea in CC. Perfusion studies in 4 patients showed net secretion of fluid and electrolytes in the colon and the small intestine and no sodium absorption in the colon [5, 6, 7]. In one of these patients, diarrhoea persisted during fasting [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonic perfu sion studies have demonstrated profuse secre tion of fluid and electrolytes in collagenous colitis. Transport of sodium appears to be pas sive, while chloride transport is active and occurs against a steep electrical gradient [29], The local prostaglandin E2 level is increased in some patients and may be the mediator in the secretory diarrhea. Ei levels have been ele vated in jejunal aspirates and stools in some patients [26].…”
Section: Pathophysiology O F Diarrheamentioning
confidence: 99%